Quantitative Trait Loci for Seed Size Variation in Cucurbits – A Review - Guo, Yu; Gao, Meiling; Liang, Xiaoxue; Xu, Ming; Liu, Xiaosong; Zhang, Yanling; Liu, Xiujie; Liu, Jixiu; Gao, Yue; Qu, Shuping; Luan, Feishi (Frontiers in Plant Science, 2020)
Cucurbits (Cucurbitaceae family) include many economically important fruit vegetable crops such as watermelon, pumpkin/squash, cucumber, and melon. Seed size (SS) is an important trait in cucurbits breeding, which is controlled by quantitative trait loci (QTL). Recent advances have deciphered several signaling pathways underlying seed size variation in model plants such as Arabidopsis and rice, but little is known on the genetic basis of SS variation in cucurbits. Here we conducted literature review on seed size QTL identified in watermelon, pumpkin/squash, cucumber and melon, and inferred 14, 9 and 13 consensus SS QTL based on their physical positions in respective draft genomes. Among them, four from watermelon (ClSS2.2, ClSS6.1, ClSS6.2 and ClSS8.2), two from cucumber (CsSS4.1 and CsSS5.1), and one from melon (CmSS11.1) were major-effect, stable QTL for seed size and weight. Whole genome sequence alignment revealed that these major-effect QTL were located in syntenic regions across different genomes suggesting possible structural and functional conservation of some important genes for seed size control in cucurbit crops. Annotation of genes in the four watermelon consensus SS QTL regions identified genes that are known to play important roles in seed size control including members of the zinc finger protein and the E3 ubiquitin-protein ligase families. The present work highlights the utility of comparative analysis in understanding the genetic basis of seed size variation, which may help future mapping and cloning of seed size QTL in cucurbits.